A new species of Hypobrycon [Characiformes: Characidae] from Uruguay basin, in Misiones, Argentina - Almirón, Adriana Edith (2001)
Fil: Almirón, Adriana Edith. Division Zoología Vertebrados, Facultad de Ciencias Naturales y Museo de La Plata - Paseo del Bosque, 1900 La Plata, Argentina